Correlation of epoxy material properties with the toughening effect of fullerene-like WS2 nanoparticles. (November 2016) - Haba, Dietmar; Brunner, Andreas J.; Barbezat, Michel; Spetter, Dmitri; Tremel, Wolfgang; Pinter, Gerald
Graphical abstract: Highlights: IF-WS2 nanoparticles can toughen certain epoxy systems, but fail to toughen others. The toughenability depends on the type and amount of curing agent used. Polyetheramine-cured epoxy systems behave entirely differently to others. Clear correlations were observed for polyetheramine-cured epoxy systems only. Abstract: This work deals with the toughening effect of inorganic, fullerene-like WS2 (IF-WS2 ) nanoparticles (NPs) on epoxy. It has been hypothesized that this toughening effect depends on the epoxy's cross-link density, its molecular defect fraction or its reference fracture toughness K Ic . Seven different epoxy systems were filled with 0.5% laboratory-made IF-WS2 NPs by mass and investigated in order to analyze which material properties are determining the toughening effect. These NPs were similar to commercially available IF-WS2 NPs, but their agglomerates could not be broken up as successfully and they yielded less toughening effect. The cross-link density of the epoxies measured via dynamic-mechanical thermal analysis agreed reasonably well qualitatively with the theoretical estimation. The glass-transition temperature and the compressive yield stress were not affected significantly by the IF-WS2 NPs. The toughening effect of IF-WS2 depended entirely on the curing agent type and quantity. Polyetheramine-cured epoxies behaved differently from the others in their yielding behavior, but also in the IF-WS2 NPs' toughening effect: While some of the investigated material properties correlate strongly with the toughening effect for polyetheramine-cured epoxies, the correlation for all investigated epoxies is rather low. Thus, none of the mentioned hypotheses could be clearly confirmed.